The Reconstruction of Economic Thought in Islam - Ali Kazmi, Aqdas (Lahore Islamic Renaissance Publishers, 2018)
This major philosophic work by one of the most important Muslim and Western religious philosophers of the 20th century continues to exert an important literary, religious, and political influence today.
Keywords: Islam -- Religious Awakening--Islam -- Islam and Philosophy -- Philosophy and Religion